Analisis Pengukuran Kinerja Rantai Pasok Dengan Menggunakan Pendekatan Model Supply Chain Operations Reference (SCOR) (Studi Kasus : Sentra Industri Batik Cap di Pekalongan, Solo, dan Yogyakarta) - Beta Viva Marga Kuasa; Aries Susanty; Wiwik Budiawan (Industrial Engineering Online Journal, 2014)
The number of batik industry is increasing while the limited availability of raw materials led to high competition among batik businesses . This growth requires the batik craftsmen to enhance and improve their performances to survive. Performance measurement is crucial to support the success of a Supply Chain Management (SCM). The implementation of SCM concepts can be seen in the center of batik industry in Pekalongan, Solo, and Yogyakarta, which are famous local producer of batik in Indonesia, but until today the center has not had any clear supply chain performance measurement systems to monitor the performance from the supplier to the consumers. Supply Chain Operations Reference (SCOR) is a conceptual model which is used to measure the performance of supply chain comprehensively and representatively. Moreover, this method can calculate the weakest link and identify opportunities for improvement . The determination of  interest priority on each  indicator uses pairwise comparisons and scoring system using SNORM de boer Based on the results of data processing, it is known that the centers which have  the highest performance values are Laweyan center (Solo ) with a value of 70.04; Kauman center ( Pekalongan ) with a value of 68.26; and Wijirejo center ( Yogyakarta ) with a value of 63.80 . The suggested recommendation is by increaseing the lowest performance indicators of each center. Keywords: Batik,  Supply Chain Operations Reference (SCOR), pairwise comparisons